1982
DOI: 10.1002/jnr.490070106
|View full text |Cite
|
Sign up to set email alerts
|

Picrotoxin action on the receptive fields of the cat sensorimotor cortex neurons

Abstract: The receptive fields of the sensorimotor cortex neurons identified by electrocutaneous stimulation were modified by microelectrophoretically applied picrotoxin which is known to reduce inhibition. a relatively short application of picrotoxin (90 nA during 3-6 min) markedly increased the size of the neuronal receptive fields in the sensorimotor cortex. Control application of glutamate showed that additional depolarization did not affect receptive fields of the spontaneously active units. Our results together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
1
9
0
Order By: Relevance
“…Similar to the mechanism revealed in the present study, inhibitory masking of sensory afferent signals has been described throughout the CNS (Metzler & Marks, ; Batuev et al . ; Merzenich et al . ; Turnbull & Rasmusson, ; Garraghty et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the mechanism revealed in the present study, inhibitory masking of sensory afferent signals has been described throughout the CNS (Metzler & Marks, ; Batuev et al . ; Merzenich et al . ; Turnbull & Rasmusson, ; Garraghty et al .…”
Section: Discussionmentioning
confidence: 99%
“…The rapid timeframe, within minutes, in which the receptive field changes occur virtually eliminates axonal sprouting and creation of new synapses as potential underlying mechanisms. Instead, it is believed that the receptive field changes reflect a release from tonic inhibition that unmasks previously latent synaptic inputs (Batuev et al 1982; Garraghty et al 1991; Jacobs & Donoghue, 1991; Wellman et al 2002; Foeller & Feldman, 2004). Masking can therefore be considered a component of the normal dynamics of the plastic brain in which neuronal responses are modified under changing stimulus conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Iontophoretic administration of γ-aminobutyric acid (GABA) blockers to neurons in somatosensory cortex showed that only a small proportion of the available excitatory input is normally expressed at any given time (Batuev et al 1982;Dykes et al 1984;Hicks and Dykes 1983). During the administration of bicuculline, a blocker of GABA receptors, the size of the receptive field of low-threshold mechanosensory neurons in cat primary somatosensory cortex increased by up to 11 times (Fig.…”
Section: Control Of Receptive Field Characteristics By Intracortical mentioning
confidence: 96%